A STUDY ON KNOWLEDGE ATTITUDE AND PRACTICE OF WOMEN OF REPRODUCTIVE AGE (15-49) YEARS ON UTILISATION OF FAMILY PLANNING SERVICES AT KASANGATI HEALTH CENTER IV WAKISO DISTRICT. A CROSS-SECTIONAL STUDY. - MBULIRO PAULINE MUTIMBA (Student's Journal of Health Research, 2023)
Introduction: This study assessed the Knowledge Attitude and Practice of Women in Reproductive Age (15-49) Years on Utilisation of Family Planning Services at Kasangati Health Center IV, Wakiso District. Methodology: A descriptive cross-sectional study involving 96 respondents who were women of reproductive age (15-49) years at Kasangati Health Center IV in Wakiso District was selected by simple random sampling technique and the data was collected by the use of self-administered questionnaires after informed consent of the respondents. Data were analyzed using the Statistical Package Social Science (SPSS) version and descriptive statistics such as frequency and percentages were used to present data on figures, charts, and tables. Findings: The majority of the respondents (58%) had knowledge about family planning and had obtained information from the health workers (70.8%), the majority (78%) knew some of the family planning methods mostly condoms (45%). Most of the respondents (70%) would not recommend their female friends to use family planning because they were not health workers (56.3%), males were responsible for making decisions concerning family planning in a family (82.3%), Conclusion: The respondents had good knowledge regarding family planning methods however their attitude towards utilization of family planning methods was poor leading to moderately low utilization of the available family planning methods and stopping the use of family planning. Recommendation: The Country's Ministry of Health, through its decentralized systems, should use health workers at the facility and at the community level to sensitize the public on family planning through various forums, including community outreach since the population is more likely to trust information from health workers.